Factors Influencing Vitamin D Levels in Neonatal Umbilical Cord Blood: A Two-Center Study From Tibet and Shenyang - Yu, Mingli; Liu, Xiuxiu; Li, Jiujun (Frontiers in Pediatrics, 2020)
Objective: To investigate the factors influencing the levels of vitamin D (vitD) in the umbilical cord blood of neonates born in Naqu, Tibet (4,500 m above sea level), and Shenyang, Liaoning Province (500 m above sea level). Methods: This prospective study was conducted from June 2017 to October 2018 in Naqu (the plateau group) and Shenyang, (the non-plateau group). Healthy mothers that gave birth to healthy neonates of >2,000g after 38 weeks’ gestation were enrolled in the study, as were their neonates. After separation of serum from the umbilical cord and mothers for routine biochemical tests, discarded samples were remained for analyses of vitD, calcium, phosphorus, alkaline phosphatase (ALP) and parathyroid hormone (PTH). Questionnaires were developed covering the demographic characteristics and possible risk factors for neonatal vitD deficiency of mothers. Statistical analysis was performed to identify associations between the calcium, phosphorus, ALP, PTH, maternal factors and neonatal vitD levels. Results: In total, 295 neonates and 225 mothers were enrolled in the study. VitD deficiency was common in neonates and mothers. The risk of vitD deficiency was higher in the plateau group than in the non-plateau group. The mean levels of 25-hydroxy vitD (25(OH)D) in mothers and neonates from the plateau group were 8.49 ± 4.12 ng/mL and 10.17 ± 5.07 ng/mL, respectively. Such levels were significantly lower than those in the non-plateau group (19.77 ± 9.57 ng/mL and 23.93 ± 11.01 ng/mL, respectively). The vitD levels of neonates and mothers were highest in the summer and lowest in the winter. Cord blood vitD was positively correlated with the vitD levels in mothers' serum (r = 0.75, P < 0.05). Increased PTH levels in mothers and decreased cord blood calcium levels were risk factors for neonatal vitD deficiency. A lack of vitD supplementation during pregnancy was associated with an 8.91-fold higher probability of neonatal vitD deficiency (OR = 8.91, 95% CI = 1.521–9.429, P < 0.001). Conclusions: The levels of neonatal and maternal vitD in the plateau group were generally lower than those in the non-plateau group. VitD supplementation during pregnancy could effectively reduce the risk of vitD deficiency in neonates.